Possessive Construction in Uab Meto - Naniana Benu (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
This paper is a result of research which is aimed to uncover the structure and marking on the possessive construction in Uab Meto based on morpho-syntax point of view. The data collected for this research were classified into the primary data (observation) and the secondary data (the data that are obtained from texts). The technique employed to analyze the data was descriptive-analytic, and the approach applied was deductive-inductive. The result of the research shows that in Uab Meto, predicative possession is expressed through the verb muiÉ â€˜have/hasâ€™. In some usages, muiÉ metathezised to muÉi. Possesive construction of Uab Meto is also applied topicalization strategy, and the last is using a verbal prefix ma-. This prefix ma- is a verbal prefix because it carries a verbal meaning, that is have/has. Furthermore, there are two attributive possessive constructions, namely juxtaposed construction. The possessor in juxtaposed constructions can be a noun or pronoun. The second attributive possessive is pronominal clitic to show the agreement with the possessors. Relating to the marking, there are only two ways, namely by juxtaposition and pertensive marker to mark the the possession. Uab Meto allows all pronouns to mark the attributive possessive relation. Without free pronoun as the possessor, a speaker Uab Meto will understand that it is a possessive noun phrase. Clitic in possession in is obligatory for inalienable possession in Uab Meto.